2014
DOI: 10.18326/rgt.v7i2.216
|View full text |Cite
|
Sign up to set email alerts
|

The Error Analysis on the Students of English Department Speaking Scripts

Abstract: Speaking skill is different from writing skill. Writing is a formal skill, so as a writer he or she must be consistently follow the formal procedures. It is different from the speaking skill which doesn't so strict in accommodating the formal rules. The Writing of script at Speaking 2 lecture is the focus of this study because the scripts are presented after they prepare for having conversation. Through writing the speaking script the students learn carefully of khow to deliver a conversation purposefully and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Comparing with the results in the study of Rini among Indonesian students, it revealed that the most dominant source of error is the ignorance of rule restrictions. However, this cause of syntactic errors is not frequent in this study [26].…”
Section: Causes Of Syntactic Errors In Oral Classroom Discoursementioning
confidence: 54%
“…Comparing with the results in the study of Rini among Indonesian students, it revealed that the most dominant source of error is the ignorance of rule restrictions. However, this cause of syntactic errors is not frequent in this study [26].…”
Section: Causes Of Syntactic Errors In Oral Classroom Discoursementioning
confidence: 54%
“…Jabeen, Kazemian, & Mustafai (2015) found out that, mostly, grammar errors produced by the students were caused by the interference of language one (L1). Those errors could be found in spoken or written utterances (Rini, 2014;Sari, 2018;Sermsook, Liamnimitr, & Pochakorn, 2017).…”
Section: Introductionmentioning
confidence: 99%